Peran Pendidikan Multikultural dalam Menumbuhkan Sikap Toleransi di Kalangan Siswa Sekolah Dasar: Kajian Literatur - Salma Murodah Putri Sasa; Nur Azmi Alwi; Inggria Kharisma (Jurnal Nakula : Pusat Ilmu Pendidikan, Bahasa dan Ilmu Sosial, 2025)
Multicultural education in elementary schools plays a crucial role in shaping students’ attitudes of tolerance. In the context of globalization, which emphasizes cultural, religious, and ethnic diversity, multicultural education aims to instill understanding and appreciation of these differences. This article seeks to examine how multicultural education can be implemented in elementary schools and its contribution to fostering students' tolerance. Through a qualitative approach with a literature review method, this study analyzes various theories and practices of multicultural education applied in elementary school settings. The findings suggest that the integration of multicultural values into the curriculum and learning activities can raise students' awareness of the importance of living together with tolerance. Therefore, multicultural education is not only about teaching differences but also serves as a means to build social peace and respect diversity in daily life.